Ambliopia anisometropia - Rares, Laya (Jurnal Biomedik : JBM, 2016)
Abstract: Anisometropic amblyopia is blurred vision due to refractive anomaly without any anatomical disorders of the eyes. It is frequently found among children in their growth and development periods. The prognosis depends on the ambylopia severity, management, patient’s obedience to the management, and age. We report a case of anisometropic amblyopia in a 8-year-old boy with his main complaint was blurred vision of both eyes. The ophthalmological examination showed the visual acuity of both eyes 6/40, PH 6/9. Several tests that showed normal results were as follows: eyeball movements to all directions; pupil responses to light; Hischberg test; cover test dan cover uncover test at near and far distance fixation; alternate cover test; and worth four dots and Maddox rod tests. Cyclopegical refraction with streak retinoscopy at 50 cm distance resulted in right eye S-4.00 C-3.00 x1800 6/9 and left eye S-1.25 C-3.25 x1800 6/7.5; autorefraction of right eye S-4.50 C-3.25 x70 and of left eye S-1.25 C-4.25 x1710. Anterior and posterior segments of both eyes were normal. Conclusion: In this case, the diagnosis was confirmed as anisometropic amblyopia and compound myopic astigmatism of the right and left eyes. The prognosis was dubia ad bonam. The patient was treated with maximal correction glasses and observed for the first four weeks, and then would be evaluated continuously untill the vision was normal. Keywords: amblyopia anisometropia, vision, refraction anomalyAbstrak: Ambliopia anisometropia merupakan gangguan penglihatan akibat kelainan refraksi tanpa disertai adanya kelainan anatomik pada mata yang sering terjadi pada masa perkembangan anak. Prognosis sangat tergantung pada derajat ambliopia, penanganan, kepatuhan pasien terhadap penanganan, dan usia pasien. Kami melaporkan kasus ambliopia anisometropia pada seorang anak berusia 8 tahun, dengan keluhan utama penglihatan kedua mata kabur. Dari pemeriksaan oftalmologik didapatkan visus ODS 6/40, PH 6/9. Beberapa pemeriksaan yang dilakukan memperlihatkan hasil normal, yaitu: pergerakan bola mata ke segala arah; respon pupil terhadap cahaya; Hischberg test; cover test dan cover uncover test pada fiksasi jarak dekat dan jauh; alternate cover test; serta worth four dots test dan Maddox rod test. Pemeriksaan refraksi sikloplegik dengan streak retinoscopy pada jarak 50 cm didapatkan mata kanan S-4,00 C-3,00 x1800 6/9 dan mata kiri S-1,25 C-3,25 x1800 6/7,5 dan pemeriksaan autorefraksi mata kanan S-4,50 C-3,25 x70 dan mata kiri S-1,25 C-4,25 x1710. Pemeriksaan segmen anterior dan posterior mata kanan dan kiri dalam batas normal. Simpulan: Diagnosis pada kasus ini ialah ambliopia anisometropia ODS dan astigmatisma miopikus kompositus ODS, dengan prognosis dubia ad bonam. Terapi yang diberikan ialah kacamata koreksi maksimal dan diobservasi selama 4 minggu pertama, dan akan dievaluasi terus sampai ketajaman penglihatan normaL. Kata kunci: ambliopia anisometropia, ketajaman penglihatan, kelainan refraksi